Does Gender Divergence Matter? The Moderating Effect of Media Exposure on Adherence to COVID-19 Quarantine Protocol - Jeong, Luz Suplico (Animo Repository, 2021)
This study aimed to find out if there are gender differences in how Filipinos adhere to the COVID-19 quarantine protocol. This research utilized the theory of planned behavior (TPB) as a framework. According to the TPB, the behavior to follow the COVID-19 protocol will be determined by one’s attitude, subjective norms, controllability, and self-efficacy. Media was added as a moderating variable between these predictors and the behavior to follow the COVID-19 protocol. An online survey was conducted amongst 200 females and 200 males in Metro Manila. This research locale was chosen as it had the highest COVID-19 infection rate in the Philippines. The study results showed no statistical differences between gender in their compliance to quarantine protocol except for attitude and controllability. These two variables and media were significant to the adherence to the COVID-19 protocol. Further, the media moderated the relationship between attitude and adherence to the COVID-19 protocol. The results showed that media exposure, whether traditional or new, moderated the adherence to quarantine protocol in both groups. This study concludes that media can be used to encourage adherence to quarantine protocol for both genders. Thus, it is recommended that marketers design the same mass media campaign to follow the quarantine protocol for both genders.